Exploring the microbial ecosystem of Berchemia polyphylla var. leioclada: a comprehensive analysis of endophytes and rhizospheric soil microorganisms - jiang, Tang Y.; xuan, Zhou S.; pin, Xiao Y.; Tao, Zhao; yan, Tao X.; GENTEKAKI, ELENI; zhi, Shi K.; xi, Lu Y.; qian, Yang Y.; yu, Zhao; tian, Zhao (Frontiers in Microbiology, 2024)
Endophytic and rhizospheric microorganisms associated with plants play a crucial role in plant health, pest and disease defense, and fruit yield by actively participating in the plant's adaptation to its environment. In this study, high-throughput sequencing technology was employed to analyze the community structure and diversity of endophytic and rhizospheric soil microorganisms in Berchemia polyphylla var. leioclada. The results revealed significant differences in microbial diversity and community structure between the soil and plant compartments within the same geographic region. Microbial diversity and species composition varied among different geographic locations. The dominant bacteria in plants were Cyanobacteria and Proteobacteria, with dominant genera including Methylobacterium-Methylorubrum, Escherichia-Shigella and Sphingomonas . In contrast, the dominant bacteria in soil were Proteobacteria, Acidobacteriota, and Actinobacteriota, with dominant genera such as Sphingomonas, Conexibacter and Vicinamibacteraceae, with Sphingomonas was considered core groups present in all plant and soil samples. As for fungi, the dominant phyla in both plants and soil were Ascomycota, Basidiomycota, and Mortierellomycota, with different dominant genera between the two compartments, including Fusarium, Septoria, and Mortierella, totaling 59 genera. Linear discriminant analysis at the genus level identified 102 bacterial and 54 fungal indicator taxa associated with plants and soil. Cooccurrence network analysis indicated close interactions among soil bacterial microorganisms. Functional prediction of the top 10 microbial genes revealed three bacterial metabolic pathways shared between soil and plants, while the predominant fungal metabolic types were similar between the two compartments but with varying abundances. This study elucidates the diversity and interplay of endophytic and rhizospheric microorganisms in Berchemia polyphylla var. leioclada across diverse geographical regions, providing insights crucial for the plant's conservation and development.